The inhibitory effects of dantrolene on action potential-induced calcium transients in cultured rat dorsal root ganglion neurons - Ayar, A; Kelestimur, H (Acad Sciences Czech Republic, Inst Physiology, 2002)
We investigated the actions of dantrolene Ca2+-induced on Ca2+-release (CICR) evoked by action potentials in cultured rat sensory neurons. The effect of dantrolene on action potential after-depolarization and voltage-activated calcium currents was studied in cultured neonatal rat dorsal root ganglion cells (DRG) using the whole-cell patch-clamp technique. Depolarizing current injection evoked action potentials and depolarizing after-potentials, which are activated as a result of CICR following a single action potential in some cells. The type of after-potentials was determined by inducing action potentials from the resting membrane potential. Extracellular application of dantrolene (10 PM) abolished after-depolarizations without affecting action potential properties. Furthermore, dantrolene significantly reduced repetitive action potentials after depolarizing current injection into these neurons, but had no significant effect on the steady-state current voltage relationship of calcium currents in these neurons. We conclude that dantrolene inhibits the induction of action potential after depolarizations by inhibiting CICR in cultured rat sensory neurons.
Keywords: dantrolene; CICR; action potential after-potentials; cultured sensory neurons; patch clamp